Los subtítulos integrados deícticos favorecen la comprensión oral en el aprendizaje de francés como lengua extranjera cuando se usan en material didáctico audiovisual - forero, monica; Moreno, Leidy J.; Bernal, Jonny F.; Torres, José D.; Martínez, Angie L. (Colombian Applied Linguistics Journal, 2022)
It has been demonstrated that subtitled multimedia content is a tool that facilitates foreign language learning. Traditionally, subtitling is presented in the lower portion of the screen, but recent research has shown the benefits of integrating subtitles within the visual image (as opposed to the bottom edge) since, by reducing the amount of eye movement, cognitive load and stress are in turn reduced, allowing for a better comprehension of the information. This research studies the potential impact of integrated (sub)titles mediated by the Gestalt laws of perception and a deictic visual effect on the oral comprehension of French as a foreign language. This study of confirmatory nature comprised two groups of French language students, to whom an oral comprehension test was applied with the purpose of comparing two stimuli: one video in French with integrated (sub)titles (stimulus 1) and the same video with integrated deictic (sub)titles (stimulus 2). The results indicate that integrated deictic (sub)titles improve oral comprehension in French language students, as they enable a better association of visual and auditory information.